Porous carbons with complex 3D geometries via selective laser sintering of whey powder - Raúl Llamas-Unzueta; Alejandro Reguera-García; Miguel A. Montes-Morán; J. Angel Menéndez (Scientific Reports)
Abstract In addition to the inherent limitations of carbons to melt or flow, a vast majority of carbon precursors deforms during carbonisation, with stereolithography of thermoset resins being the preferred technology for 3D printing of carbons. An alternative is now presented with the possibility of using a melting-based technology, selective laser sintering (SLS), to fabricate 3D structures that withstand carbonisation. The key factor that makes this happen is whey powder, a natural, abundant and cheap by-product of the dairy industry. When heating the whey powder with a laser at 180–200 ºC for a few seconds, whey particles sinter, and 3D structures are obtained layer-by-layer. Carbonisation of the sintered whey structures brings about 3D porous carbons with excellent mechanical properties that preserve the SLS printed form albeit an isotropic shrinkage (approx. 23%). Melanoidins are identified as responsible for both the sintering and the thermoset behaviour during carbonisation of the whey powder.